Moderate Sedation Versus General Anesthesia for Endobronchial Ultrasound-guided Transbronchial Biopsy in an Academic Training Center. Issue 2 (4th March 2020) - Ronaghi, Reza; Kareem, Waasil; Yaghmour, Bassam; Mahdavi, Ramyar
Abstract : Endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) is a widely used procedure for the diagnosis and staging of lung cancer. Several studies have shown the diagnostic utility of EBUS-TBNA effectiveness for decreasing the need for invasive mediastinal sampling. The current recommendation is that most patients with lung cancer should undergo mediastinal staging with EBUS-TBNA. EBUS-TBNA can be safely performed under general anesthesia or moderate sedation, and, according to previous studies, the choice of anesthesia on the effect of outcomes has been variable. We investigated differences between EBUS-TBNA performed with general anesthesia and moderate sedation in a training program in which trainees performed EBUS-TBNA. This retrospective study evaluated 121 patients undergoing fellow-driven EBUS-TBNA under the supervision of an interventional pulmonary trained faculty member. We found no difference between general anesthesia and moderate sedation in terms of diagnostic yield, procedural time, or complication rates. We did, however, find an overall higher number of total lymph nodes sampled in the general anesthesia group, as well as a higher number of hilar lymph nodes sampled. We conclude that EBUS-TBNA can be performed safely and with good diagnostic ability with either general anesthesia or moderate sedation in a fellowship-driven program without affecting overall outcomes. This is beneficial, as it can reduce overall cost and the ability to do the procedure without the need of an anesthesiologist.